Proteomic analysis from haploid and diploid embryos of Quercus suber L. identifies qualitative and quantitative differential expression patterns. (Proteomics, 2009)
Quercus suber L. is a Mediterranean forest species with ecological, social and economic value. Clonal propagation of Q. suber elite trees has been successfully obtained from in vitro-derived somatic and gametic embryos. These clonal lines play a main role in breeding and genetic studies of Q. suber. To aid in unravelling diverse genetic and biological unknowns, a proteomic approach is proposed. The proteomic analysis of Q. suber somatic and gametic in vitro culture-derived embryos, based on DIGE and MALDI-MS, has produced for the first time proteomic data on this species. Seventeen differentially expressed proteins have been identified which display significantly altered levels between gametic and somatic embryos. These proteins are involved in a variety of cellular processes, most of which had been neither previously associated with embryo development nor identified in the genus Quercus. Some of these proteins are involved in stress and pollen development and others play a role in the metabolism of tannins and phenylpropanoids, which represent two of the major pathways for the synthesis of cork chemical components. Furthermore, the augmented expression levels found for specific proteins are probably related to the homozygous state of a doubled-haploid sample. Proteins involved in synthesis of cork components can be detected at such early stages of development, showing the potential of the method to be useful in searching for biomarkers related to cork quality.